High‐temperature ferroelectricity and strong magnetoelectric effects in a hybrid organic–inorganic perovskite framework. Issue 1 (18th November 2014) - Tian, Ying; Stroppa, Alessandro; Chai, Yi‐Sheng; Barone, Paolo; Perez‐Mato, Manuel; Picozzi, Silvia; Sun, Young
<x xml:space="preserve">Abstract</x> A Cu‐based organic–inorganic perovskite framework exhibits high‐temperature ferroelectricity with strong magnetoelectric effects. Both electric field control of magnetization and magnetic field control of polarization are realized. Theoretical calculations suggest that a new mechanism of hybrid improper ferroelectricity arising from the Jahn–Teller distortions of magnetic metal ions and tilting of the organic cations are responsible for the peculiar multiferroic behaviors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> A Cu‐based perovskite organic–inorganic framework showing high‐temperature improper ferroelectricity. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)